In-Stent Restenosis and a Drug-Coated Balloon: Insights from a Clinical Therapeutic Strategy on Coronary Artery Diseases - Dai-Min Zhang; Shaoliang Chen (Cardiology Research and Practice)
Coronary heart disease is a major cause of death and disability in developed countries. Stent implantation has become an efficacious treatment for a culprit lesion vessel of the coronary artery. However, 10%–20% restenosis is still an important complication that restricts the clinical safety and efficacy of drug-eluting stents. In-stent restenosis may lead to the recurrence of major cardiovascular adverse events, including angina pectoris, acute myocardial infarction, and even sudden cardiac death. These events are currently serious problems that occur after coronary stent implantation. Clinical physicians face a difficult choice for in-stent restenosis treatment. Recent studies indicate that a drug-coated balloon has promising clinical efficacy similar to the drug-eluting stents for treating coronary in-stent restenosis. Therefore, in this study, we highlight the progress of coronary intervention and the use of drug-coated balloons in the treatment of in-stent restenosis (ISR).